1984
DOI: 10.1111/j.1365-2222.1984.tb02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Airborne endotoxins and humidifier disease

Abstract: The presence of humidifier disease in a printing factory was investigated with particular emphasis on airborne endotoxins. The water in the humidifier was contaminated with Pseudomonas. The amount of airborne endotoxin when the humidifier was operating was 0-13-0-39 jug/m^ Twenty of the fifty workers investigated reported typical symptoms of fever, chills, and chest tightness when the humidifiers were operating. Symptoms were more frequent among non-smokers.The estimated inhaled dose of endotoxin was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 14 publications
1
44
0
2
Order By: Relevance
“…Inhalation of air contaminated with gram-negative bacteria results in toxic pneumonitis characterized by fever, chills, and chest tightness, which may be encountered in humidifier disease (38) or during occupational exposures. Lipopolysaccharide (LPS)/endotoxin, a component of the outer membrane of gram-negative bacteria, is one of the primary constituents of organic dust.…”
mentioning
confidence: 99%
“…Inhalation of air contaminated with gram-negative bacteria results in toxic pneumonitis characterized by fever, chills, and chest tightness, which may be encountered in humidifier disease (38) or during occupational exposures. Lipopolysaccharide (LPS)/endotoxin, a component of the outer membrane of gram-negative bacteria, is one of the primary constituents of organic dust.…”
mentioning
confidence: 99%
“…The reports of bath water fever and humidifier lung demonstrated high concentrations of endotoxin (0. 1-5.0 |Lig/ml) in the causative water (13,14). Endotoxin is an extremely potent agent of lung injury and the inhalation of endotoxin can cause symptomssuch as chills and fever, a decrease in DLC0, an increase in airway hyperresponsiveness, and increases in neutrophils as well as lymphocytes in BALand blood, in a dose-dependent fashion (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the onset of symptomsin the present case occurred immediately following the use of the humidifier for the first time favors this notion. It has been suggested that bacterial endotoxin may play a role in humidifier lung (12)(13)(14)(15). The reports of bath water fever and humidifier lung demonstrated high concentrations of endotoxin (0.…”
Section: Discussionmentioning
confidence: 99%
“…Humidifier disease has been documented in an occupational setting where airborne endotoxin levels ranged from 130 to 390 ng/m 3 (Rylander & Haglind 1984 …”
Section: Introductionmentioning
confidence: 99%